AGW613- Management And Organizational Behaviour (September 1997) - PPP, Pusat Pengajian Pengurusan (1997)
Master of Business Administration First Semester Examination Academic Session 1997 / 98 September 1997 AGW613- MANAGEMENT AND ORGANIZATIONAL BEHAVIOUR Time : [3 hours] INSTRUCTIONS: Please make sure that this examination paper consists of FOUR (4) printed pages before you begin. Answer question ONE (1) and any other EIGHT (8) questions.